Historical drivers and future streamflow variations of the Kura River in the Western Transcaucasia region of Georgia: Analysis of tree-ring chronologies from 1720 to 2021 CE - Bakhtiyorov, Zulfiyor; Chen, Feng; Chen, Youping; Wang, Shijie; Zhang, Heli; Hu, Mao; Yue, Weipeng; Habibulloev, Sharifjon; Kavtaradze, Giorgi; Gurskaya, Marina; Agafonov, Leonid; Rahmonov, Oimahmad; et al. (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
In this paper, we conduct a dendrochronological study in the Western Transcaucasia region of Georgia to elucidate the relationship between tree growth and climatic variables (temperature, precipitation, and streamflow) in order to reconstruct the paleohydrology of the Kura River and to assess the impacts of climate change on water resources. We analyzed tree-ring chronologies from 1720 to 2021 CE, and analysis of July–August streamflow revealed five wet phases (1739–1753, 1764–1807, 1811–1831, 1962–1988 and 2000–2019 CE ranging in duration from 11 to 49 years) when streamflow exceeded the long-term mean, and four dry phases (1720–1738, 1832–1881, 1936–1961 and 1989–1999 CE) when streamflow was below average. The most extreme wet and dry years were 1771 and 1851 CE, respectively. Spatial correlation patterns of Kura River reconstructed runoff against sea level pressure (SLP) are negative in the Arctic and positive in mid- to high-latitude Eurasia. The Arctic Oscillation (AO)/North Atlantic Oscillation (NAO), and solar activity are important drivers of hydroclimatic conditions in the Mediterranean region, by modifying the location of high-pressure areas and large-scale atmospheric circulations. Comparison of our Kura streamflow reconstructions and data in the Old World Drought Atlas (OWDA) reveals a moderately positive correlation (0.40) throughout the study period, being strongest over the Southern Caucasus and Eastern Turkey. This validates the drought signals and emphasizes the importance of using multi-proxy approaches, supported by spatially resolved data, to enhance understanding of regional hydroclimatic variability and drought patterns. We additionally conducted future streamflow scenarios, most notably under the high-emission SSP585 scenario, in line with global trends in CMIP6 projections. Our streamflow results indicate a trend towards increasing drought severity, which highlights the need for urgent adaptation and mitigation strategies in water resource management in this region. Ultimately, this study provides valuable information on historical hydroclimatic conditions in the Kura River Basin, which help to develop strategies to mitigate the hydrologic impacts of climate change in the Western Transcaucasia Caucasus region. We further highlight the importance of regional and global teleconnections for understanding regional hydrological dynamics. •The study reconstructed Kura River's streamflow (1720–2021) and identifying 24 dry and 17 wet years linked to climate variations.•Synoptic climatology analyses have revealed that shifts in the Arctic Oscillation (AO)/North Atlantic Oscillation (NAO) and solar activity significantly affect Mediterranean hydroclimatic conditions and large-scale atmospheric circulations, thereby influencing streamflow and regional climate variability.•Projected CMIP 6 runoff decreases: 14.91 % by century's end under moderate emissions, and 35.68 % by 2100 under high emissions, signaling severe future drought risks.